2013
DOI: 10.1371/journal.pone.0067216
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Heat Shock Protein 60 as a Regulator of Neutral Sphingomyelinase 2 and Its Role in Dopamine Uptake

Abstract: Activation of sphingomyelinase (SMase) by extracellular stimuli is the major pathway for cellular production of ceramide, a bioactive lipid mediator acting through sphingomyelin (SM) hydrolysis. Previously, we reported the existence of six forms of neutral pH–optimum and Mg2+-dependent SMase (N-SMase) in the membrane fractions of bovine brain. Here, we focus on N-SMase ε from salt-extracted membranes. After extensive purification by 12,780-fold with a yield of 1.3%, this enzyme was eventually characterized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Effects of nSMase2 on normal synaptic regulation was studied in models of dopamine uptake where it was shown that nSMase2 inhibition or downregulation by siRNA decreased dopamine uptake in PC12 cells (Kim et al , 2010) with Hsp60 acting as an interaction partner that negatively regulates nSMase2 in that system (Ahn et al , 2013). This paved the way to more in depth studies of involvement of nSMase2 in dopaminergic pathologies such as Parkinson’s disease.…”
Section: Nsmase2 As a Regulator Of Biological Functionsmentioning
confidence: 99%
“…Effects of nSMase2 on normal synaptic regulation was studied in models of dopamine uptake where it was shown that nSMase2 inhibition or downregulation by siRNA decreased dopamine uptake in PC12 cells (Kim et al , 2010) with Hsp60 acting as an interaction partner that negatively regulates nSMase2 in that system (Ahn et al , 2013). This paved the way to more in depth studies of involvement of nSMase2 in dopaminergic pathologies such as Parkinson’s disease.…”
Section: Nsmase2 As a Regulator Of Biological Functionsmentioning
confidence: 99%
“…3A , lower panel). A previous study reported that nSMase2 directly interacts with Hsp60 via negative regulation ( Ahn et al, 2013 ); hence, we examined whether mt-iSMase binds to Hsp60. Mitochondrial and synaptosomal fractions were immunoprecipitated using anti-Hsp60 and anti-c-Myc antibodies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies have shown that Nsm is also regulated by heat shock protein 60 and by the phosphatase calcineurin (44,45). Although calcineurin has been previously shown to be involved in mycobacterial infections, it is presently unknown whether calcineurin also plays a role in mycobacteria-induced activation of Nsm (46).…”
Section: Discussionmentioning
confidence: 99%